Associations of early pregnancy high-sensitivity C-reactive protein levels with subsequent gestational diabetes: A Finnish gestational diabetes study - Shilpa Lingaiah; Marja Vääräsmäki; Hanna Öhman; Eero Kajantie; Elina Keikkala; Sanna Mustaniemi (Diabetology & Metabolic Syndrome)
Abstract Background High sensitivity C-reactive protein (hsCRP) is a sensitive marker of subclinical inflammation and has been proposed as a marker for predicting gestational diabetes in early pregnancy. However, data concerning the levels of hsCRP in early pregnancy are inconsistent. We aimed to determine hsCRP levels in early pregnancy and to examine the associations between hsCRP levels and the number of abnormal values in the oral glucose tolerance test and the type of hyperglycemia. Methods Early pregnancy serum hsCRP levels were analyzed in 776 women with gestational diabetes and 856 pregnant controls without diabetes. The mean gestational age at sampling was 10.7 weeks. Results Early pregnancy hsCRP levels were higher in women who later developed gestational diabetes compared to controls (geometric mean 3.71 mg/L vs. 2.62 mg/L). After adjustments, including those for maternal age and pre-pregnancy body mass index, the results remained significant. When compared to the lowest quartile of hsCRP, women in the other quartiles had 1.5-fold odds for gestational diabetes after adjustments. Furthermore, hsCRP levels were higher in women with two or three abnormal oral glucose tolerance test values compared to those with one abnormal value and among women with postprandial hyperglycemia compared to those with only fasting hyperglycemia. Conclusion Early pregnancy serum hsCRP levels were associated with subsequent gestational diabetes, and most with a higher number of abnormal values and postprandial hyperglycemia in the oral glucose tolerance test. These findings highlight the role of chronic inflammation and clustering of metabolic risk factors involved in gestational diabetes and its severity.